Rehabilitation Trends After Lower Extremity Amputations in Canada. Issue 5 (21st September 2016) - Kayssi, Ahmed; Dilkas, Steven; Dance, Derry L.; de Mestral, Charles; Forbes, Thomas L.; Roche‐Nagle, Graham
Abstract: Background: The heterogeneity of medical complications that lead to amputation has resulted in a diverse patient population with differing rehabilitation needs; however, the rehabilitation trends for patients with lower extremity amputations across Canada have not been studied previously. Objective: To describe trends in rehabilitation after lower extremity amputations and the factors affecting rehabilitation length of stay in Canada. Design: Retrospective cohort analysis. Setting: Canadian inpatient rehabilitation facilities that received persons with lower extremity amputations discharged from academic or community hospitals. Participants: Patients underwent lower extremity amputations between 2006 and 2009 for nontraumatic indications and were then discharged to a rehabilitation facility. Patients were identified from the Canadian Institute for Health Information's Discharge Abstract Database that includes hospital admissions across Canada except Quebec. Interventions: Inpatient rehabilitation after lower extremity amputations. Main Outcome Measures: Length of stay, discharge destination, and change in total and motor function scores. Results: The analysis included 5342 persons who underwent lower extremity amputations, 1904 of whom were transferred to a rehabilitation facility (36%). Patients most commonly underwent single below‐knee (74%) and above‐knee (17%) amputations. The duration of rehabilitation varied by whether the amputation was performed by a vascular (median = 36 days), orthopedic (median = 38 days), or general surgeon (median = 35 days). The overall median length of stay was 36 days. Most patients (72%) subsequently were discharged home and 9% were readmitted to hospital. Predictors of longer rehabilitation included amputation by an orthopedic surgeon (beta = 5.0, P ≤ .01), older age (beta = 0.2, P ≤ .01), and a history of ischemic heart disease (beta = 3.8, P = .03) or congestive heart failure (beta = 5, P = .04). Patients who spent <7 days in hospital were significantly more likely to have a shorter rehabilitation stay (beta = −4, P = .03). Advanced patient age was the only predictor for hospital readmission (odds ratio = 1.03, P ≤ .01). Conclusions: Rehabilitation length of stay in Canada after lower extremity amputation varies by the type of surgeon performing the amputation. Advanced age, undergoing surgery in the province of Manitoba, and having a history of ischemic heart disease or congestive heart failure predict a longer rehabilitation stay. A shorter perioperative hospitalization period (<7 days) predicts a shorter rehabilitation duration. Future studies are needed to explore these issues and to optimize the delivery of rehabilitation services to Canadians after lower extremity amputation. Level of Evidence: II